A comparative study of electrochemical battery for electric vehicles applications - Habib, A K M Ahasan; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (IEEE, 2020)
In Green transportation system, electric vehicle (EV) has become one of the most proficient technologies. In EV automotive industries, energy storage system is the most important sector to economic and ecological issues. Electrochemical battery technology is a fundamental category of EV and has a great market for energy storage system. It is essential to recognize system cost and lifetime, descend from the difficulty of assembly a high- power, high-energy, energy density, and flexible electrochemical system of electrochemical energy storage technologies. In this paper a rigorous study on EV application battery properties, formation, and comparison on advantages and disadvantages. It is observed that some batteries have good feature to run the EV. Green transportation system needs a smart energy storage system. Hopefully, in this review the feature of different types of batteries will be highlighted that will lead to choose the battery system in the EV application.